Effect of Internet of Things on Competitive Edge in the Rwandan Telecommunication Landscape: A Case of MTN Rwandacell PLC - Kabanda, Aimable; Njenga, Samson (International Journal of Strategic Management, 2024)
Purpose: In the competitive landscape of Rwanda's telecommunication industry, information security has emerged as a critical factor in maintaining and enhancing market position. The general objective of this study was to investigate the effect of IoT implementation strategies on competitive edge in the Rwandan telecommunication landscape. Specifically, the study determined the effect of information security on competitive edge in the Rwandan telecommunication landscape. Methodology: The research design that the study utilized is descriptive survey research. The target population for this study comprised 187 participants who are currently employed as staff at MTN Rwanda. A sample of 128 were determined using Slovin’s Formula. A stratified sampling technique was employed in the investigation. In this project, questionnaires with closed-ended questions and a five-point Likert scale style was used as the main data gathering instruments. The information was gathered via secondary data collected from a variety of sources, with individuals being requested to fill out questionnaires that were provided. Thirteen individuals made up the sample size for this initial inquiry. Using Cronbach's Alpha, the researcher conducted the reliability assessment. A group of accomplished professionals in the area of strategic management assessed the reliability and validity of the instruments. Using SPSS version 25, the researcher conducted a comprehensive analysis of the data using both qualitative and quantitative methods. The study used a correlation coefficient and a linear regression model. Data presentation was done in Tables and figures. Findings: The regression model reveals several significant predictors of competitive edge within the telecommunications landscape. Notably, integration with existing systems emerges as a substantial negative predictor (β = -0.395, p < .001), indicating that challenges in integrating IoT technologies with legacy systems may hinder competitiveness. In conclusion, the regression analysis highlights the critical role of integration with existing systems and data analytics in shaping competitive edge within the Rwandan telecommunications landscape. While challenges in integrating IoT technologies with legacy systems may pose obstacles, the transformative potential of data-driven decision-making emerges as a significant driver of organizational performance and competitiveness. Unique Contributions to Theory, Practice and Policy: Based on the findings, it is recommended that telecommunication companies in Rwanda prioritize investments in data analytics capabilities to enhance competitive edge and strategic decision-making. Additionally, efforts should be directed towards streamlining integration processes with existing systems to mitigate barriers and capitalize on the potential of emerging technologies, thus fostering innovation and sustainable growth within the industry. This study contributes to theory by providing empirical evidence on the impact of IoT adoption on competitive advantage in the telecommunications sector, particularly within a developing country context. Practically, it offers actionable insights for MTN Rwandacell Plc to enhance operational efficiency and service delivery, while also informing policymakers on the regulatory frameworks needed to support IoT innovation in Rwanda.